Exploratory Factor Analysis (EFA) to measure entrepreneur satisfaction - Dedi, Iskamto; Puspa Liza, Ghazali; Asyraf, Aftanorhan; Jenita, Jasman; Sukono, .; Abdul Talib, Bon (2020)
This paper reports on developing a conceptualization for measuring the satisfaction of entrepreneurs. The paper, in doing so, first establishes a theoretical framework by defining constructs of entrepreneur satisfaction from the literature. Secondly, the identification of evaluating requirements from the literature for these constructs, and thirdly, the validation of the theoretical model for measuring the satisfaction of entrepreneurs in Indonesia. The theoretical model consists of 9 entrepreneur satisfaction. The empirical process of validation employed data collected from 100 respondents of pilot test what Micro and Small Enterprises in Pekanbaru Indonesia. The validation method aimed at validating the parameters which measure each of the constructs by statistically determining that the sample used is adequate, using the Bartlett test to ensuring the usefulness of the data for multivariate statistical analysis, validating the measurement requirements as applicable to entrepreneur satisfaction and determining the reliability of each entrepreneur satisfaction. All those goals were accomplished. This coincided in the end result, perhaps even an adjusted statistical model to measure the satisfaction of entrepreneurs in Indonesia. The design has been statistically tested to become a valid and reliable design.